Creative Thinking : An Islamic Perspective - Badi, Jamal; Tajdin, Mustapha (International Islamic University Malaysia, 2005)
Enthusiastic readers, notably those who have special interest in thinking and cognition, are expected to know a great deal on creativity both as a skill and as a discipline. However, rare are those who have thoughts on what a religion like Islam has to say about it. Many vital fields of studies seem to have been alienated from religious principles and values, as if religion distrupts the smoth and triumphant march of human knowledge. This book presents a humble argument for the worth of Islamic principles and values in the domain of thinking and creativity. Though this work is an introductory textbook devised for teaching purposes, it hopes to meet the expectations of those who seek detailed and informative account of the subject.